A PET study with [11C]AZ10419369 to determine brain 5-HT1B receptor occupancy of zolmitriptan in healthy male volunteers. (July 2013) - Varnäs, Katarina; Jučaitė, Aurelija; McCarthy, Dennis J; Stenkrona, Per; Nord, Magdalena; Halldin, Christer; Farde, Lars; Kanes, Stephen
Aim: To investigate the occupancy at brain 5-hydroxytryptamine (5-HT) 1B receptors in human subjects after administration of the antimigraine drug zolmitriptan. Methods: Positron emission tomography (PET) studies were undertaken using the radioligand [ 11 C]AZ10419369 in eight control subjects at baseline and after administration of zolmitriptan orodispersible tablets. The subjects were examined after two consecutive administrations of 10 mg zolmitriptan, approximately 1 week apart. Two of the subjects were subsequently examined after administration of 5 mg zolmitriptan. One week after the last administration of zolmitriptan five of the subjects underwent additional PET measurements without drug pretreatment. Results: After administration of 10 mg zolmitriptan, mean receptor occupancy was 4–5%. No consistent changes in 5-HT1B receptor binding were observed for subjects who received 5 mg zolmitriptan. There was a statistically significant negative relationship between binding potential ( BP ND ) and plasma concentration of zolmitriptan and the active metabolite 183C91, respectively. All of the five subjects who were examined 1 week after dosing with zolmitriptan showed higher BP ND post drug administration compared with baseline. Conclusion: This is the first demonstration of CNS 5-HT1B receptor occupancy of a triptan. The findings are consistent with the low receptor occupancy previously reported in PET studies with agonists at other G protein coupled receptors.